African Rural And Agricultural Credit Association - Central Bank of Nigeria and Afraca Member Institutions in Nigeria (Lagos Finacial Institutions Training Centre, 1996)
relevance of self-help groups as viable channels for saving mobilisationand credit delivery in Nigeria.